ESCALATION READING COMPREHENSION ON NARRATIVE TEXT BY USING WORD SEARCH PUZZLE GAME TO THE FIRST YEAR STUDENTS OF SMA NEGERI 1 SAMALANGA (A Collaborative Classroom Action Research): ESCALATION READING COMPREHENSION ON NARRATIVE TEXT BY USING WORD SEARCH PUZZLE GAME TO THE FIRST YEAR STUDENTS OF SMA NEGERI 1 SAMALANGA (A Collaborative Classroom Action Research) - LISMAYANTI LISMAYANTI; MISNAWATI MISNAWATI (Journal of English Education and Social Science, 2021)
The research of using word search puzzle game in developing the students’ reading comprehension has been done at SMA Negeri 1 Samalanga, Bireuen District. It was begun from August 8th 2020 until August 27th 2020.The scope of this research focus on escalation reading comprehension on narrative text by using word search puzzle game. This research is designed as collaborative classroom action research with four steps, namely: planning the action, implementing the action, observing the action, and reflecting the action and has two cycles. There are four kinds of instruments which use to collect the data needed in this research, namely: observation checklist for the teacher and the students, test that consist of pre-test and post-test, questionnaires, and field note. The data has been collected and was analyzed through qualitative and quantitative analysis. The research was conducted for the second-year students. The number of samples are 20 students. The data analysis showed that the mean score of students in post-test in cycle is 58,5, although the mean score has not achieved the criteria of success, but it showed that a significant difference with the pre- test, the score in pre-test was 56. Because the criteria of success have not been achieved in cycle I, the researcher continued the second cycle to get an optimal result for the students’ achievement. The result showed that the score of the students in post-test in cycle II was 79. Its mean that the research was success. Based on the evidence, it could be concluded that word search puzzle game could be used in the teaching reading comprehension to improving the students’ reading comprehension.